A study to introduce National Early Warning Scores (NEWS) in care homes: Influence on decision‐making and referral processes. Issue 1 (15th November 2021) - Hodgson, Philip; Greaves, Jane; Cook, Glenda; Fraser, Angela; Bainbridge, Lesley
Abstract: Aim: Early warning scores are commonly used in hospital settings, but little is known about their use in care homes. This study aimed to evaluate the impacts of National Early Warning Scores alongside other measures in this setting. Design: Convergent parallel design. Methods: Quantitative data from 276 care home residents from four care homes were used to analyse the relationship between National Early Warning Scores score, resident outcome and functional daily living (Barthel ADL (Barthel Index for Activities of Daily Living)) and Rockwood (frailty). Interviews with care home staff ( N  = 13) and care practitioners ( N  = 4) were used to provide qualitative data. Results: A statistically significant link between National Early Warning Scores ( p  = .000) and Barthel ADL ( p  = .013) score and hospital admissions was found, while links with Rockwood were insignificant ( p  = .551). Care home staff reported many benefits of National Early Warning Scores, including improved communication, improved decision‐making and role empowerment. Although useful, due to the complexity of the resident population's existing health conditions, National Early Warning Scores alone could not act as a diagnostic tool.